FABRICATION OF MICROEMULSION LOADED SUBLINGUAL FILM FOR RAPID ABSORPTION OF FENTANYL CITRATE IN TRANSIENT BREAKTHROUGH PAIN - MUNDHEY, D.; SAPKAL, N.; DAUD, A. (International Journal of Applied Pharmaceutics, 2021)
Objective: The present research work aims to develop a microemulsion loaded sublingual film for rapid absorption of fentanyl citrate in transient breakthrough pain. Methods: The Fentanyl citrate microemulsion loaded sublingual film was prepared using Capmul MCM C8 (oil), tween 20 (surfactant) and propylene glycol (co-surfactant) with different grades of film-forming polymer (HPMC) using a film casting machine. The films were evaluated for in vitro disintegration study, tensile strength, folding endurance, content uniformity, drug content, in vitro dissolution, pH, thickness and weight variation, scanning electron microscopy, ex vivo permeation study, droplet size, polydispersity index, zeta potential, % moisture content and stability study were evaluated. Results: The optimized film formulation showed desired mechanical properties (tensile strength of 0.291 kg/cm2) and a minimum disintegration time of 20 s. The optimized sublingual film formulation exhibited 43.16 % of FC microemulsion loading. Morphological study showed the absence of drug crystals on the polymeric surface. Permeation studies through goat sublingual mucosa indicated 89% fentanyl citrate release through fentanyl citrate microemulsion loaded sublingual film, whereas only 40% fentanyl citrate release was obtained when it was directly added to film without microemulsion strategy. Conclusion: The present study indicated that extend of permeation of fentanyl citrate when added to the sublingual film in microemulsion form was around 2.225 folds higher than when added directly to film without microemulsion. The present microemulsion embedded film technology could be a promising alternative to conventional drug delivery systems and traditional routes of administration for breakthrough pain management.